CD4+ T-lymphocytes exhibit biphasic kinetics post-myocardial infarction - Kumar, Vinay; Prabhu, Sumanth D.; Bansal, Shyam S. (Frontiers in Cardiovascular Medicine, 2022)
CD4+ T-cells facilitate wound healing post-myocardial infarction (MI) but promote left-ventricular (LV) remodeling during ischemic heart failure (HF; 8 weeks post-MI). Therefore, it is critical to understand if sustained CD4+ T-cell activation leads to this pathological response, or if phenotypically different T-cells are activated during MI vs HF. Using flow cytometry, we found that cardiac CD4+ T-cells exhibit two distinct patterns of transmigration. First pattern consisted of a rapid CD4+ T-cell response with maximal levels seen at 3d post-MI which return to baseline by 14d. However, during HF we observed a 2nd phase of activation and CD4+ T-cells were 20-fold higher in HF as compared to sham-operated mice. Importantly, these biphasic kinetics were observed with all major T-cell subsets such as Th1, Th2, Th17 and regulatory T-cells suggesting a global change. To determine the role of this 2nd peak of T-cell activation, CD4-iDTR mice were generated and treated with DT every 10 days from 28 days post-MI to deplete CD4+ T-cells during chronic HF. While littermate control mice showed increased end-systolic and end-diastolic volumes (ESV and EDV) and decreased ejection fraction (EF) from 4 to 8 weeks post-MI, depletion of CD4+ T-cells in Cre+ mice significantly blunted LV remodeling and inhibited progressive increases in the EDV and ESV, and reduction in EF. This suggests that CD4+ T-cell responses occurring during HF are different than those occurring during MI and promote LV remodeling and progressive cardiac dysfunction. Temporal immunomodulation of CD4+ T-cells could be a translatable modality for ischemic HF.